2010
DOI: 10.1007/s00595-009-4173-8
|View full text |Cite
|
Sign up to set email alerts
|

Do Japanese thoracic surgeons think that dissection of the pulmonary ligament is necessary after an upper lobectomy?

Abstract: It is uncertain whether the dissection of the pulmonary ligament is necessary in patients who undergo an upper lobectomy. A questionnaire was sent to the directors of Thoracic Surgery in 102 hospitals, asking whether dissection of the pulmonary ligament is performed in such patients, and the complications associated with dissecting or preserving the ligament. Seventy-eight directors (76%) returned the questionnaire. The preservation of the ligament is the current practice in 54 hospitals (69%), while 13 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 1 publication
0
13
1
Order By: Relevance
“…Currently, many thoracic surgeon dissect IPLs during superior lobectomy, which can reduce the residual cavity of the chest and prevent atelectasis, but which also induces risks of bronchial distortion, stenosis, obstruction, and even ventilation dysfunction (9,12). A study from Japan has shown that 69% of hospitals preserve IPLs during superior lobectomy, and that the doctors in these hospitals think that preservation of IPLs can reduce the incidence rate of bronchial distortion and stenosis, but will increase the risks of pleural effusion and infection (13). In the present study, there was no significant difference in terms of complication rate, chest drainage, drainage time, and delayed air leak.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Currently, many thoracic surgeon dissect IPLs during superior lobectomy, which can reduce the residual cavity of the chest and prevent atelectasis, but which also induces risks of bronchial distortion, stenosis, obstruction, and even ventilation dysfunction (9,12). A study from Japan has shown that 69% of hospitals preserve IPLs during superior lobectomy, and that the doctors in these hospitals think that preservation of IPLs can reduce the incidence rate of bronchial distortion and stenosis, but will increase the risks of pleural effusion and infection (13). In the present study, there was no significant difference in terms of complication rate, chest drainage, drainage time, and delayed air leak.…”
Section: Discussioncontrasting
confidence: 44%
“…No mortality or conversion to open surgery was observed in the present study, while previous series in which the IPLs were dissected observed a mortality rate of 0.5-3.7% and a conversion rate of 1.8-17.6% (21,22). In these previous series, the most common complication was air leak, which was observed in two patients from group D. When preserving the IPLs, the most common complications are pleural effusion, insufficient lung expansion, atelectasis, empyema, pneumonia, pooling of sputum and fistula (13). In the present study, one case of arrhythmia, two with pneumonia, and one with atelectasis were observed.…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, the whole drainage time was not obviously prolonged, which might be also affected by other factors, such as different numbers, diameters of chest tubes, and different volume thresholds for chest tube removal used among studies. A questionnaire survey conducted by Usuda et al [4] in Japan has revealed that nearly 28% directors in the Department of Thoracic Surgery tend to attribute the pooling of pleural effusion to the preservation of IPL. However, a recent study performed by Kim et al [11] has stated that no significant difference is found between the preservation and dissection groups in terms of delayed pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…During upper lobectomy, whether the inferior pulmonary ligament (IPL) should be dissected remains a controversial issue. A traditional view has suggested that the dissection of IPL can improve the reexpansion of the inferior lobe, obliterate the free place in thoracic cavity, and then reduce the accumulation of pleural effusion [4, 5]. However, several other studies have also stated that the dissection of IPL can lead to the excessive bronchial displacement, which may be associated with the chronic dry cough or even other fatal outcomes postoperatively [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…In patients undergoing second lung cancer surgery, special caution is required regarding bronchial displacement after previous surgery [1]. Particularly, patients after a left upper lobectomy commonly have U-or V-shaped angulation of the left main bronchus [2][3][4][5]. Although a standard left-sided double-lumen tube (DLT) is most commonly used to achieve one-lung ventilation (OLV), patients after a left upper lobectomy may encounter ventilation failure with this tube due to bronchial angulation [5].…”
Section: Introductionmentioning
confidence: 99%